A blue-hued mystery: primaquine-induced methemoglobinemia in mixed infection with Plasmodium vivax and Plasmodium falciparum - Zainulabid, Ummu Afeera; Cheong, Xiong Khee; Periyasamy, Petrick; Mohd Salleh, Ahmad Firdaus; Ghazali, Nurraffini; Hassan, Noor Wanie; Sangaran, Kumuthamalar; Mohd Yassin, Azlin; Md Idris, Zulkarnain (Elsevier, 2025)
Primaquine-induced methemoglobinemia is a rare but serious adverse effecect, typically observed in patients with glucose-6-phosphate dehydrogenase (G6PD) deficiency. Although G6PD screening is routinely performed before primaquine administration, methemoglobinemia can still occur in patients with normal G6PD activity. This case highlights the importance of recognizing this rare complication in patients with mixed ma- laria infections, even in the absence of known risk factors, and underscores the role of molecular diagnostics in confirming the infecting species.